Countering Corruption in Modern Russia - Moiseev, Vladimir Victorovich; Aleksandrovna, Molchanova Marina; Sergeevna, Polovneva Lyudmila; Ivanovich, Kramskoy Sergei; Pastukh, Tamara Alexandrovna; Frantsevich, Nitsevich Victor (Journal of Ecohumanism, 2024)
The problem of combating corruption is of particular relevance in Russia. In the 2023 global anti-corruption ranking, Russia took a lowly 137th place between Paraguay and Kyrgyzstan. The authors sought not only to reveal the reasons for its unprecedented growth in the last two decades, but also to show how anti-corruption policy is set up in the country and what the real results of the anti-corruption fight are. Using factual material, the authors show the true reasons for the unprecedented growth in the scale of corruption, point out significant shortcomings in anti-corruption policy and Russian legislation, and identify ways to improve them for the purpose of further socio-economic development. The results of the study not only give an idea of how the situation has developed in the Russian Federation with the growth of corrupt practices, but can also provide real assistance in modernizing anti-corruption policy and changing the current federal legislation in order to strengthen the fight against the theft of money from the state budget. The value of this research is that it contributes to the development of theory and methods of combating corruption in government structures.